2022
DOI: 10.3390/biomedicines10112907
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Targeted Sodium Chlorite (NP001) Slows Progression of Amyotrophic Lateral Sclerosis (ALS) through Regulation of Microbial Translocation

Abstract: Amyotrophic lateral sclerosis (ALS) is a heterogeneous, progressive, and universally fatal neurodegenerative disease. A subset of ALS patients has measurable plasma levels of lipopolysaccharide (LPS) and C-reactive protein (CRP) consistent with low-grade microbial translocation (MT). Unless interrupted, MT sets up a self-perpetuating loop of inflammation associated with systemic macrophage activation. To test whether MT contributed to ALS progression, blood specimens from a phase 2 study of NP001 in ALS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Biomarker levels for specimens collected at baseline and end of study plasma were evaluated at the same time by the commercial company AssayGate, Inc. (Ijamsville, MD, USA). An extensive biomarker analysis was recently reported using specimens from this trial and baseline values of biomarkers fell within the expected range of those reported in the literature related to patients with ALS [ 31 ].…”
Section: Methodssupporting
confidence: 63%
See 4 more Smart Citations
“…Biomarker levels for specimens collected at baseline and end of study plasma were evaluated at the same time by the commercial company AssayGate, Inc. (Ijamsville, MD, USA). An extensive biomarker analysis was recently reported using specimens from this trial and baseline values of biomarkers fell within the expected range of those reported in the literature related to patients with ALS [ 31 ].…”
Section: Methodssupporting
confidence: 63%
“…Clearly, a larger properly powered placebo-controlled trial would need to be performed in order to test the theory that clinical VC responses to NP001 would be related to regulation of the innate immune system. The data presented in this and two previous papers analyzing clinical data from NP001 phase 2 trials [ 28 , 31 ] identified plasma CRP levels as critical to apparent clinical responsiveness to NP001. Given that CRP is an acute phase reactant, inherently variable plasma CRP levels that differ between patients can confound results tied to the selection of patients with slightly elevated CRP values.…”
Section: Limitations Of the Current Studymentioning
confidence: 68%
See 3 more Smart Citations